2000
DOI: 10.1677/jme.0.0250243
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of rainbow trout (Oncorhynchus mykiss) estrogen receptor-alpha messenger RNA and its expression in the ovary during the reproductive cycle

Abstract: This study developed a quantitative reverse transcription-polymerase chain reaction (RT-PCR) method to measure estrogen receptor-(ER ) mRNA in the rainbow trout (Oncorhynchus mykiss). Using RT-PCR, and primers based on the known ER DNA sequence in this species, cDNA sequences representing most of the protein coding region were obtained from ovary poly A(+) RNA. Using these DNA sequences as probes in Northern blot hybridizations confirmed that a single transcript of 4·2 kilobases in poly A(+) RNA could be detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 30 publications
4
17
0
Order By: Relevance
“…As gonadal development progressed, the expression levels of all three ntERs declined. Similar observations have been reported in rainbow trout follicles where ERa mRNA was detectable in very immature follicles and was rapidly down-regulated as oocyte development progressed (Nagler et al 2000). Future studies on the cellspecific expression pattern of each ER are required for better elucidation of the molecular mechanism of estrogen receptor-mediated effects on male reproduction.…”
Section: Discussionsupporting
confidence: 79%
“…As gonadal development progressed, the expression levels of all three ntERs declined. Similar observations have been reported in rainbow trout follicles where ERa mRNA was detectable in very immature follicles and was rapidly down-regulated as oocyte development progressed (Nagler et al 2000). Future studies on the cellspecific expression pattern of each ER are required for better elucidation of the molecular mechanism of estrogen receptor-mediated effects on male reproduction.…”
Section: Discussionsupporting
confidence: 79%
“…In higher phyla estrogens and their receptors (ER) acquired an indispensable role in the reproductive organs, where controlled the mechanisms leading to the maturation of the egg, and in the liver, where became essential for vitellogenin synthesis (Della Torre et al, 2014;Flouriot et al, 1997;Flouriot et al, 1996;Hayward et al, 1982;May et al, 1981;Nagler et al, 2000;Pakdel et al, 1991;Takase and Iguchi, 2007). Supporting this view, from anguilliformes to mammals, ER expression or activity is highest in ovaries and liver (Ciana et al, 2003;Griffin et al, 1999;Nagler et al, 2000;Todo et al, 1996). In addition, studies in female mouse showed a specific synchrony of ER transcriptional activity in liver and reproductive tissues (Ciana et al, 2003;Della Torre et al, 2011a) with a rhythm imposed by the reproductive cycle.…”
Section: The Mechanisms Subjecting Fertility To Nutrient Availabilitymentioning
confidence: 99%
“…The mRNAs for the four ER isoforms (ERa1, ERa2, ERb1, ERb2) were quantified using primers and protocols for quantitative reverse transcription polymerase chain reaction originally described in Nagler et al [21]. Enhanced green fluorescent protein complementary RNA generated by in vitro transcription was used as an internal standard to account for amplification differences between samples, because an endogenous gene could not be found that consistently amplified in samples of both the liver and the ovary.…”
Section: Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…Enhanced green fluorescent protein complementary RNA generated by in vitro transcription was used as an internal standard to account for amplification differences between samples, because an endogenous gene could not be found that consistently amplified in samples of both the liver and the ovary. Generation of the enhanced green fluorescent protein plasmid and application of the in vitro transcription protocol were as described in Nagler et al [21]. Messenger RNA levels for all target genes and the enhanced green fluorescent protein internal standard were determined using absolute quantities calculated from standard curves as described in Nagler et al [21].…”
Section: Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
See 1 more Smart Citation